Synthesis of nanochitosan from oyster pearl shell (Pinctada maxima) as renewable energy candidate - Rahayu, Susi; Alawiyah, Geby; Kurniawidi, Dian W.; Ardianto, Teguh; Budianto, Arif; Alaa, Siti; Syamsuddin, Syamsuddin (Acta Chimica Asiana, 2024)
The increase in energy needs must be balanced by environmentally friendly technological innovations. Chitosan polymer is one of the technological innovations of energy materials that are being developed by many developed countries. This research aimed to identify the potential of oyster pearl shell waste as a source of electrolyte polymers. The study was conducted experimentally by synthesizing chitosan nanoparticles from chitosan using the ionic gelation method. Chitosan is obtained through the isolation method from Pinctada maxima oyster pearl shell waste. The isolation method is carried out by three processes: deproteination, demineralization, and deacetylation. Several characterizations were carried out to analyze the material from the synthesis, including a proximate test, FTIR analysis, and PSA analysis. Isolated chitosan was identified to have a deacetylation degree that reached 88.63% with the formation of OH and NH2 functional groups. In general, the proximate tets data has shown that the obtained chitosan already meets the Indonesian standard SNI 7949:2013. PSA analysis resulted in differences in size distribution, PDI, and zeta potential between chitosan and chitosan nanoparticles. The results were obtained by the average distribution of chitosan particle size of 52.043 μm and chitosan nanoparticle size of 2.3365 μm—the analysis of the potential zeta of chitosan -3.9 mV and chitosan nanoparticle -21,6 mV. Thus, changes in the size of the chitosan material affect its potential PDI and zeta values. The change of these two values is a good indicator of the initial data and the potential of the material as an energy material. Therefore, chitosan polymer is an electrolyte material that can be used as a candidate for environmentally friendly renewable energy materials